The Hidden History of Crime, Corruption, and States - Renate Bridenthal (Berghahn Books, 2013)
A specter is haunting history. The ghostly presence of economic crime as political power has been all but absent in history writing, but not in history itself. Like dark matter, its synergy has been palpable if not always visible. Yet in our time, more and more emerges from the shadows, exposed in newspapers and tried in courts, and compels us to consider the history of the illicit political economy and its effects in past and present.Here we venture to do so by specific examples. Three conceptsâ€”crime, corruption, and statesâ€”all hard to define and historically variable, are examined by ten authors writing about different places in different epochs. Our claim that there is a hidden history in the history of states and state making refers to the fact that most established narratives do not analyze how lawmakers and lawbreakers have been intrinsically connected, indeed dialectically involved in shaping each other.1 From Augustineâ€™s observation in the fourth century that kingdoms and robber bands were essentially the same, to Charles Tillyâ€™s insight in our own time that â€œbanditry, piracy, gangland rivalry, policing, and war-making all belong on the same continuum,â€ we have been aware of the similarity of these forces.2 Yet historians have tended to write more respectable stories about the formal development of states and the overt challenges to them, such as revolutions. They have not acknowledged economic crime, which so easily and amorally changes sides, as having a bearing on significant historical transformations. Too often described as a marginal phenomenon, or a shadow that accompanies important political events, it becomes nearly weightless ephemera or material for novelists.